FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI IUD DI KLINIK BERSALIN BUDI MULIA MEDIKA PALEMBANG TAHUN 2013 - Tirta Anggraini Tirta Anggraini (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2014)
ABSTRACT [Indonesia is the country with the largest population among the member countries of ASEAN (Association of Southeast Asian Nations) with a population of more 243.3 million. In Indonesia as many as the number of participants IUD KB 3933611 (11.12%). In South Sumatra planning acceptors IUD 56 027 (4.36%). In Palembang in 2011 the number of participants KB IUD 6,971 (4.44%). At the Maternity Clinic Budi Mulia Medika Palembang in 2012 the number of participants KB IUD 105 (18.6%). The purpose of this study is be knew the factors associated with the use of IUD Contraception in Maternity Clinic Budi Mulia Medika Palembang in 2013. This study uses the Analytic Survey cross-sectional approach. The population in this study were all active acceptors who visit to get family planning services at the Maternity Clinic Budi Mulia Medika Palembang in May - June 2013, earned a total of 32 respondents. Sampling was carried out by the technique of "accidental sampling". Univariate analysis of the results obtained from the use of IUD 10 respondents (31.2%) were not using IUDs and 22 (68.8%), respondents who were at high risk of 9 (28.1%), and highly educated respondents 13 (40 , 6%), and high economic bersosial respondents 10 (31.2%). From bivariate analysis using chi-square test P value = 0.013 obtained showed no statistically significant association between maternal age and the use of contraceptive IUD obtained P value = 0.005 showed no significant relationship between education and the use of IUDs and contraceptive P value = 0.037 showed no significant relationship between socioeconomic IUD contraceptive use in the Maternity Clinic Budi Mulia Medika Palembang in 2013. From the results of this study should be conducted counseling or counseling to all about the importance of family planning acceptors IUD is a long-term contraception. ABSTRAK Indonesia adalah negara dengan penduduk terbanyak di antara negara anggota ASEAN (Association of Southeast Asia Nation) lainnya dengan jumlah penduduk 243,3 juta jiwa. Di indonesia jumlah peserta KB IUD sebanyak 3.933.611 (11,12%). Di Sumatera Selatan jumlah peserta KB IUD 56.027(4,36%). Di Palembang tahun 2011 jumlah peserta KB IUD 6.971(4,44%). Di Klinik Bersalin Budi Mulia Medika Palembang tahun 2012 jumlah peserta KB IUD 105 (18,6%). Tujuan penelitian ini adalah Di ketahuinya faktor-faktor yang berhubungan dengan penggunaan Kontrasepsi IUD di Klinik Bersalin Budi Mulia Medika Palembang Tahun 2013. Penelitian ini menggunakan metode Survey Analitik dengan pendekatan Cross Sectional. Populasi pada penelitian ini adalah semua akseptor KB aktif yang berkunjung untuk mendapatkan pelayanan KB di Klinik Bersalin Budi Mulia Medika Palembang pada bulan mei – juni 2013, didapatkan sebanyak 32 responden. Pengambilan sampel ini dilaksanakan dengan teknik “Accidental Sampling”. Dari analisis univariat didapatkan hasil responden yang menggunakan IUD 10 (31,2%) dan yang tidak menggunakan IUD 22(68,8%), responden yang berumur resiko tinggi 9 (28,1%), dan responden yang berpendidikan tinggi 13 (40,6%), serta responden yang bersosial ekonomi tinggi 10 (31,2%). Dari analisis bivariat dengan menggunakan uji chi-square didapat P value = 0,013 menunjukkan ada hubungan bermakna antara umur ibu dengan penggunaan kontrasepsi IUD dan didapat P value = 0,005 menunjukkan ada hubungan bermakna antara pendidikan dengan penggunaan kontrasepsi IUD serta P value = 0,037 menunjukkan ada hubungan bermakna antara sosial ekonomi dengan penggunaan kontrasepsi IUD di Klinik Bersalin Budi Mulia Medika Palembang Tahun 2013. Dari hasil penelitian ini seharusnya dilakukan penyuluhan atau konseling terhadap semua akseptor KB tentang pentingnya KB IUD yaitu alat kontrasepsi jangka panjang.